Nutrient Uptake of Paddy with Peat Humic Substance Application on Tidal Swamp - Yartiwi, Yartiwi; Ghulamahdi, Munif; Sulistyono, Eko; Lubis, Iskandar; Sastro, Yudi (AGRIVITA Journal of Agricultural Science, 2025)
Numerous initiatives were carried out to enhance rice production in swampy areas, which required the implementation of suitable technology. The use of adaptive variety, soil, and water management have been reported as the main keys to agricultural culture on tidal swamps. Therefore, this study was conducted to analyze the effect of several levels of substance peat humic application on the growth and yield of rice in tidal swamps. A completely randomized design was also used with two factors and four replications between March to June 2022, in Karya Bakti, Rantau Rasau sub-district of Tanjabtim District, Jambi Province. The first factor was varieties IR-64 and Inpara-4, while the second was the use of humic substance in peat consisting of 0 g/plant, 0.04 g/plant, 0.08 g/plant, and 0.12 g/plant. The cultivation process included the planting of paddy seeds within buckets containing 10 kg of soil. The result showed that the optimal yield of rice varieties IR-64 and Inpara-4, when subjected to peat humic substance in saturated soil culture, was achieved at 0.12 g/plant. This was substantiated by the enhanced uptake of essential nutrients such as N, P, and K in the plants, resulting in superior plant biomass compared to other concentration levels.